2012
DOI: 10.5861/ijrsll.2012.190
|View full text |Cite
|
Sign up to set email alerts
|

The English split infinitive: A comparative study of learner corpora

Abstract: The split infinitive in English has been controversial for over a century. Whilst a prescriptive grammar rule forbids infinitive splitting, it seems that modern grammar academics, as well as users, accept and allow for its occurrence. The approval of split-infinitive structure has also been clearly substantiated by plenty of convincing linguistic evidence: real data from native-speaker corpora confirms its existence in different varieties of English. The present study, using the data collected from Thai Learne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Nonetheless, there are studies that have indicated that there might be differences among proscribed features in terms of their frequency in academic prose. Most notably, split infinitives, while commonly proscribed by style guides, have been found to occur with moderate frequencies, indicating a shift toward increased acceptance of this feature (e.g.,Perales-Escudero, 2011;Supakorn, 2013). We may therefore expect this feature to behave somewhat differently from the other two proscribed features.Examining novice writers' perceptions of formality…”
mentioning
confidence: 94%
“…Nonetheless, there are studies that have indicated that there might be differences among proscribed features in terms of their frequency in academic prose. Most notably, split infinitives, while commonly proscribed by style guides, have been found to occur with moderate frequencies, indicating a shift toward increased acceptance of this feature (e.g.,Perales-Escudero, 2011;Supakorn, 2013). We may therefore expect this feature to behave somewhat differently from the other two proscribed features.Examining novice writers' perceptions of formality…”
mentioning
confidence: 94%